The Effect of Common Milkweed (Asclepias syriaca) Quality on Monarch Butterfly (Danaus plexippus) Oviposition Preference and Larval Performance - Gilmour, Sydney (Université d'Ottawa / University of Ottawa, 2021)
Species are experiencing shifts in their phenology (i.e., seasonal timing of recurring biological events) due to climate change, leading to disruptions in the relative timing of interacting species. These shifts can be detrimental to the fitness of the consumer (e.g., herbivore) in the interaction. In its larval form, the monarch butterfly (Danaus plexippus) is a specialist herbivore that feeds on milkweed plants (Asclepias spp.). Given that plants generally experience seasonal declines in quality, it is hypothesized that if climate change disrupts the timing of the larval stage relative to the availability of younger milkweed plants, monarch performance will be negatively affected. In this thesis, I explore the potential for negative consequences for the eastern monarch population due to potential shifts in the timing of their interaction with milkweed—due to phenological shifts in either species. I used field surveys around Ottawa, ON to determine monarch oviposition preference on common milkweed (Asclepias syriaca) plants and the seasonal availability of their preferred plants. To determine the potential consequences for monarch fitness where females oviposit on non-preferred plants, I conducted a field experiment to assess the effect of milkweed size on monarch larval performance. Based on field surveys, females preferentially oviposited on smaller milkweed plants in earlier developmental stages with low levels of discolouration. Plants in early developmental stages were consistently available in large proportion over the summer season. These results suggest that even if the relative timing of the monarch-milkweed interaction in the eastern population is shifted due to climate change, there will likely be suitable milkweed plants available for oviposition throughout the breeding season, which could act as a buffer to disruptions in the relative timing of the interaction. I found that bigger plants exuded more latex and had thicker leaves than smaller plants. However, larval performance was unaffected by these plant quality differences. While it is unclear how the relative timing of the monarch-milkweed interaction will change in the future, my results suggest that shifts in the relative timing of their interaction within the breeding season are unlikely to have negative consequences for larval performance in eastern Ontario. Future studies should determine how the relative timing of the interaction will change in the region and explore how climate change will affect the quality of milkweed plants.
Keywords: Phenology; Leaf quality; Monarch butterfly; Common milkwed; Plant-insect interactions